La identidad de «des-exilio»: el caso de María Zambrano - Wachowska, Judyta (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2004)
This article is a voice in understaning the problem of Spanish «dis-exile» from a perspective shown by Maria Zambrano. In her various writings one can follow a strict line of her philosophical thinking dedicated to the individual and historical consciouseness that an exiled person can recover when he/she starts his/her journey to an unknown future: his/her soul is crossed by signs of centuries. That is why an exile, and dis-exile as its consequence, can become an apparent contra-diction: the fact of being deprived of a common and obvious reality lets reach one's origins of identity. Maria Zambrano herself was exilied for forty five years between 1939 and 1984 and this experience became an essential dimension of her life.
The identity of «disexile »: the case of Maria Zambrano